2015
DOI: 10.1002/lary.25659
|View full text |Cite
|
Sign up to set email alerts
|

Utility of preoperative computed tomography and magnetic resonance imaging in adult and pediatric cochlear implant candidates

Abstract: 4 Laryngoscope, 126:1440-1445, 2016.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 20 publications
1
36
0
2
Order By: Relevance
“…Such ossification has been intraoperatively confirmed by several studies [Quaranta et al, 2005;Tamplen et al, 2016;Vashishth et al, 2017]. Vashishth et al [2017] found that although 60.5% (23/38 ears) of their cohort of CI users with otosclerosis had evidence of ossification, many nonetheless had good auditory outcomes.…”
Section: Findings In Subjects With Otosclerosismentioning
confidence: 68%
See 1 more Smart Citation
“…Such ossification has been intraoperatively confirmed by several studies [Quaranta et al, 2005;Tamplen et al, 2016;Vashishth et al, 2017]. Vashishth et al [2017] found that although 60.5% (23/38 ears) of their cohort of CI users with otosclerosis had evidence of ossification, many nonetheless had good auditory outcomes.…”
Section: Findings In Subjects With Otosclerosismentioning
confidence: 68%
“…The occurrence of facial nerve stimulation in CI recipients with otosclerosis is well known [Bigelow et al, 1998;Seyyedi et al, 2013;Tamplen et al, 2016]. It has been suggested that in cases of otosclerosis, the impedance of the otic capsule is reduced and this increases the potential diffusion of electrical current through the bone.…”
Section: Facial Stimulationmentioning
confidence: 99%
“…Lin et al reported that 40 % of children with severe to profound SNHL had abnormal MRI findings and 24 % had MRI findings that could explain their hearing loss [25]. The higher diagnostic yield of MRI relative to CT must be balanced with the increased cost associated with MRI and the need for sedation and additional time compared with CT. 2014 Medi-Cal reimbursement rates for a CT temporal bone were $212, $953 for an MRI of the IAC, and $250 for sedation during the exam [28]. …”
Section: Medical Evaluationmentioning
confidence: 99%
“…Computed tomographies (CTs) and magnetic resonance imagings (MRIs) have been traditionally used to evaluate cochlear implant (CI) candidates. The utility of preoperative imaging in pediatric CI candidates is well documented because anatomic abnormalities can alter surgical planning in up to 20% of cases . However, the utility of preoperative imaging is yet to be determined in adult CI candidates with postlingual deafness.…”
Section: Introductionmentioning
confidence: 99%